Evaluation method for regional development level of big data - Hui AN; Jinxin ZHUANG; Yiming LI (大数据)
Implementing the national big data strategy and promoting the development and application of big data,is becoming the focus of the work of local governments in China.And there is an urgent need for specific guidance with pertinence and operability.The significance of research on evaluation method for regional development level of big data was explained,the difficulties faced in the evaluation were analyzed,innovative solutions were designed,the overall design of index system and evaluation mechanism evaluation method was proposed,and the direction and the focus for further work was put forward.